Profit Sharing and Pension Plans/ Profit Sharing and Pension Plans (Book). - Smith, Frank P.; Morgner, A. (The Accounting Review, 1948)
Abstract Reviews two books "Profit Sharing and Pension Plans (Practical Planning and Administration)," by C. Morton Winslow and "Profit Sharing and Pension Plans (Law and Taxes)," by K. Raymond Clark.